ONLINE LEARNING BASED ON CONSTRUCTIVISM TO SUPPORT UNIVERSITAS TERBUKA DISTANT LEARNERS (Jurnal TEKNODIK, 2022)
This article will elaborate on the possibility of implementing constructivism learning theories in designing an online learning tutorial program that will support and facilitate distance learning students to build better knowledge and skills. Universitas Terbuka (UT), an Indonesian state university that implements a distance learning system, conducts an online learning program to support the students’ learning process. The use of digital and network technology has significant effects on the human learning process. It changes the paradigm of learning and instruction. Recently, by using digital and network technology, students can learn without facing the restriction of time and place. In addition, the students can use various learning resources and materials to support their efforts in gaining knowledge and skills. The use of constructivism theory in online learning is expected to enable students to widen their knowledge and sharpen their skills while learning. This study uses a research and development approach to create a constructivist online learning program that can facilitate distance learning students' achieving their learning objectives.